Invisible Canons: The Presence and Availability of Graphic Novel Adaptations of Literary Classics in University Libraries - Tekin, Eda; Ilhan, Genc Osman; Kir, Durmus Baris (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Despite the increasing pedagogical value of graphic novel adaptations of classic literary works, there is limited research investigating their availability in university libraries, especially in non-English-speaking countries. This study explores the presence of graphic novel adaptations of canonical literature in university libraries across Istanbul, Turkey. Using a qualitative document analysis method, library catalogs from 13 major public and private universities were systematically examined. Data were collected through keyword searches (e.g., graphic novel, graphic novel adaptation) and analyzed based on physical and electronic availability, format diversity, and author/title frequency. The findings reveal a significant scarcity of such adaptations in academic collections. While some institutions, such as Bo & gbreve;azi & ccedil;i University, hold a modest range of adaptations (e.g., Macbeth, A Midsummer Night's Dream), most university libraries lack even the most widely adapted classics (e.g., Jane Eyre, Frankenstein, Crime and Punishment). The findings indicate that graphic novel adaptations are limited in academic library collections. Only three of the thirteen universities surveyed held canonical graphic novel adaptations: Bo & gbreve;azi & ccedil;i University (13 titles), Galatasaray University (3 titles), and & Idot;stanbul University (2 titles). This limited availability can restrict students' access to multimodal reading experiences and potentially hinders the development of visual literacy and critical reading skills. Moreover, the high price of imported graphic novels makes access even more difficult. The study highlights the need for inclusive collection development policies that reflect contemporary literacy practices. It contributes to the growing discourse on equitable access to alternative literary formats and offers implications for educators, librarians, and policymakers aiming to enhance multimodal literacy through academic resources.
Keywords: Access equity; collection development; graphic novel adaptation; literature; university libraries; visual literacy; READING-COMPREHENSION; COMIC-BOOKS; NOVELS; DIRECTIONS; STUDENTS; Information Science & Library Science